2004
DOI: 10.3141/1899-11
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Height Affects Drivers’ Speed Perception: Implications for Rollover Risk

Abstract: The North American vehicle fleet has evolved in recent years to include an increasing percentage of pickups, sport utility vehicles (SUVs), and minivans. In 2002, sales of light trucks and vans accounted for almost half of all Canadian vehicle sales. The increased popularity of SUVs has been particularly striking, with a 143% increase in sales since 1993. Typically larger and heavier than automobiles, SUVs are built on frames that are more rigid and that ride higher, characteristics that not only provide incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
(9 reference statements)
2
10
0
1
Order By: Relevance
“…Although this effect is typically explained by other, higher-level factors, our study suggests that the rich detail landscapes might cause internal time to run faster due to the higher number of changes, causing participants to drive slower to keep their subjective speed at comfortable levels. A similar finding that links the subjective perception of speed with interval timing is reported in Rudin-Brown ( 2004 ) who has shown that eye height of a driver affects preferred speed, with drivers seated higher preferring faster speeds caused by the subjectively slower movement of the outside world. As suggested by a reviewer, an elegant test that could provide further links between laboratory tasks and task-settings with higher external validity is to compare conditions with meaningful semantic visual context versus phase-scrambled movies, which would make the current experiment better comparable to laboratory studies in which semantically irrelevant movement is provided.…”
supporting
confidence: 80%
“…Although this effect is typically explained by other, higher-level factors, our study suggests that the rich detail landscapes might cause internal time to run faster due to the higher number of changes, causing participants to drive slower to keep their subjective speed at comfortable levels. A similar finding that links the subjective perception of speed with interval timing is reported in Rudin-Brown ( 2004 ) who has shown that eye height of a driver affects preferred speed, with drivers seated higher preferring faster speeds caused by the subjectively slower movement of the outside world. As suggested by a reviewer, an elegant test that could provide further links between laboratory tasks and task-settings with higher external validity is to compare conditions with meaningful semantic visual context versus phase-scrambled movies, which would make the current experiment better comparable to laboratory studies in which semantically irrelevant movement is provided.…”
supporting
confidence: 80%
“…They found only small effects in terms of speed underestimation for higher camera positions. Similar results are observable when drivers have to judge their own speed while driving in larger vehicles: ego-speed is underestimated when seated in a van or truck, as compared to a sedan (Panerai et al, 2001; Rudin-Brown, 2004). However, these results might also be attributable to an increased feeling of safety when driving with a large vehicle and give no direct information about the perception of distance.…”
Section: Introductionmentioning
confidence: 66%
“…The ''bigger is safer'' attitude makes SUV drivers more likely to believe in any benefits relating to a larger vehicle, even if these benefits are illusory. For example, SUV drivers are more likely to accept a safety advantage from the increased visibility of a taller vehicle, even though a taller vehicle is likely to block the view of other drivers (Rudin-Brown, 2004), have greater blind spots, have a higher center of gravity, and be more prone to rollover and loss of control accidents (Kweon and Kockelman, 2003;Wenzel and Ross, 2005). The acceptance of illusory benefits is not due to an impaired knowledge of vehicle size and safety, as car drivers have a similar knowledge when tested.…”
Section: Discussionmentioning
confidence: 98%
“…However, Rudin-Brown (2004) found that headway to a lead vehicle increases when the lead vehicle is large, indicating driver compensation to the reduction in sight distance caused by the large vehicle. Individual safety gains relative to other drivers may be regarded as ''selfish safety,'' where a driver can obtain self-protection in a larger vehicle with a higher level of occupant safety in a multiple-car collision and a better line of sight of the road ahead.…”
Section: Introductionmentioning
confidence: 89%